Gas diffusion electrode

CN123036688APending Publication Date: 2026-11-03TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023980.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-17
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing gas diffusion electrodes in polymer electrolyte fuel cells have the problem of balancing water drainage and conductivity, which can easily lead to flooding and affect power generation performance.

Method used

A microporous layer containing carbonaceous particles and fluorinated hydrophobic resin is formed on a conductive porous substrate. The ratio of fluorine to carbon (F/C) on the surface of the microporous layer is controlled within a specific range to ensure both drainage and conductivity.

Benefits of technology

This approach achieves full drainage of the microporous layer surface without compromising gas diffusion and conductivity, thereby suppressing flooding and improving the power generation performance of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A gas diffusion electrode of one embodiment of the present application is a gas diffusion electrode having a microporous layer containing carbonaceous fine particles and a fluorine-based hydrophobic resin on at least one side of an electrically conductive porous substrate. In the gas diffusion electrode, the surface layer F / C of the side surface of the microporous layer which is not in contact with the electrically conductive porous substrate is 0.35 or more and 0.60 or less. The surface layer F / C is the ratio of fluorine to carbon detected by scanning electron microscope-energy dispersive X-ray spectrometry (SEM-EDX) at an acceleration voltage of 2.0 kV at a field of view of 1000 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a gas diffusion electrode used in fuel cells, and particularly to a gas diffusion electrode used in a polymer electrolyte type fuel cell that is also used as a power source for fuel cell vehicles, etc. Background Technology

[0002] A fuel cell is a device that extracts the energy generated when hydrogen and oxygen react to produce water in the form of electricity. It has high energy efficiency and the only emission is water, so it is expected to be a clean energy source.

[0003] A polymeric electrolyte fuel cell, which supplies hydrogen-containing fuel gas to the anode and oxygen-containing oxidizing gas to the cathode, generates an electromotive force through an electrochemical reaction occurring at both electrodes, is typically constructed by sequentially stacking a separator, a gas diffusion layer, a catalyst layer, an electrolyte membrane, another catalyst layer, a gas diffusion layer, and a separator. The electrodes used in a polymeric electrolyte fuel cell are sandwiched between two separators, and the polymeric electrolyte membrane has a structure consisting of a catalyst layer formed on the surface of the polymeric electrolyte membrane and a gas diffusion layer formed on the outer side of the catalyst layer. A gas diffusion electrode flows through the membrane as a separate component for forming the gas diffusion layer. Required properties for the gas diffusion electrode include, for example, gas diffusivity, conductivity, and water permeability. To obtain a gas diffusion electrode with excellent performance in these areas, a conductive porous substrate that combines gas diffusivity and conductivity is generally used.

[0004] A fuel cell is a system that extracts the energy generated when hydrogen and oxygen react to produce water in the form of electricity, thus increasing the electrical load. Specifically, increasing the current drawn from the fuel cell to the outside will produce a large amount of water (water vapor). If this water vapor condenses into droplets at low temperatures, these droplets can clog the pores of the gas diffusion electrode, reducing the supply of gas (oxygen or hydrogen) to the catalyst layer. If all the pores of the gas diffusion electrode eventually become clogged, the fuel cell will stop generating electricity (a phenomenon known as flooding). To minimize flooding, the gas diffusion electrode requires drainage. Typically, a gas diffusion electrode substrate that has undergone hydrophobic treatment on a conductive porous substrate is used to improve its drainage (hydrophobicity).

[0005] However, if a hydrophobically treated conductive porous substrate, as described above, is used directly as a gas diffusion electrode, large water droplets are generated during water vapor condensation due to the roughness of its fibers, making it prone to flooding. Therefore, sometimes a microporous layer containing conductive particles such as carbon black is formed on a hydrophobically treated conductive porous substrate.

[0006] The microporous layer is a component of the gas diffusion electrode, and therefore, in addition to drainage, it must also possess conductivity, just like the conductive porous substrate. However, it is known that the drainage and conductivity required for a gas diffusion electrode are generally in a contradictory (trade-off) relationship. To overcome this contradiction, many measures have been taken to improve the drainage and conductivity of the gas diffusion electrode and thus enhance its power generation performance by changing the structure and materials in the microporous layer.

[0007] For example, Patent Document 1 proposes a gas diffusion electrode characterized in that the microporous layer has a first microporous layer and a second microporous layer in contact with a conductive porous substrate, and by making the hydrophobic resin contained in the first microporous layer more than that contained in the second microporous layer, it has high adhesion to the catalyst layer and high conductivity.

[0008] In addition, Patent Document 2 proposes a gas diffusion electrode that reduces the resistance in the thickness direction by using carbon black and graphite particles with an aspect ratio of 10 or more in a microporous layer.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: Japanese Patent No. 6766650

[0012] Patent Document 2: International Publication No. 2023 / 190153 Summary of the Invention

[0013] The problem that the invention aims to solve

[0014] However, while the gas diffusion electrode described in Patent Document 1 has improved adhesion to the catalyst layer, the insufficient amount of fluororesin on the outermost surface of the microporous layer results in inadequate drainage, sometimes leading to flooding. Furthermore, the need to form two microporous layers also presents challenges in terms of productivity.

[0015] The gas diffusion electrode described in Patent Document 2 reduces the amount of fluororesin in order to improve the conductivity in the microporous layer. As a result, the amount of fluororesin on the outermost surface of the microporous layer is small, and the drainage is insufficient, which sometimes leads to water flooding.

[0016] Therefore, the object of the present invention is to provide a gas diffusion electrode that can maintain high conductivity while ensuring sufficient drainage of the microporous layer surface, thereby suppressing flooding when used in fuel cells.

[0017] Problem-solving methods

[0018] In order to solve the above problems and achieve the objectives, the present invention has the following configuration as described in any one of [1] to [5].

[0019] That is, the gas diffusion electrode of the present invention is [1]: a gas diffusion electrode, characterized in that it has a microporous layer containing carbonaceous particles and fluorinated hydrophobic resin on at least one side of a conductive porous substrate.

[0020] The surface F / C ratio of the microporous layer on the side that is not in contact with the conductive porous substrate is greater than 0.35 and less than 0.60. The surface F / C is the ratio of fluorine to carbon, which is determined by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) at an accelerating voltage of 2.0 kV and a field of view of 1000x.

[0021] Furthermore, the gas diffusion electrode of the present invention is [2]: the gas diffusion electrode as described in [1] above, characterized in that the F / C of the outermost 10 nm of the surface of the microporous layer that is not in contact with the conductive porous substrate is 0.62 or more and 0.80 or less, and the F / C of the outermost 10 nm is determined by X-ray photoelectron spectroscopy, i.e., ESCA, when the excitation X-ray is a monochromatic Al Kα at 1486.6 eV. 1,2 The ratio of fluorine to carbon was determined under conditions of 200 μm X-ray beam diameter and 45° photoelectron detection angle.

[0022] Furthermore, the gas diffusion electrode of the present invention is [3]: the gas diffusion electrode as described in [1] or [2] above, characterized in that the O / C ratio of the outermost 10 nm of the surface of the microporous layer that is not in contact with the conductive porous substrate is 0.01 or less, and the O / C ratio of the outermost 10 nm is determined by X-ray photoelectron spectroscopy (ESCA) with a monochromatic Al Kα excitation X-ray of 1486.6 eV. 1,2 The ratio of oxygen to carbon was determined under conditions of 200 μm X-ray beam diameter and 45° photoelectron detection angle.

[0023] Furthermore, the gas diffusion electrode of the present invention is [4]: ​​a gas diffusion electrode as described in any of [1] to [3] above, characterized in that the resistance in the normal direction (i.e., the thickness direction) when compressed under a pressure of 2.4 MPa is 5.5 mΩ·cm. 2 the following.

[0024] Furthermore, the gas diffusion electrode of the present invention is [5]: a gas diffusion electrode as described in any of [1] to [4] above, characterized in that the contact angle between the surface of the microporous layer that is not in contact with the conductive porous substrate and the mixture formed by mixing isopropanol and water in a mass ratio of 1:2 is 35° or more and 80° or less.

[0025] Invention Effects

[0026] According to the gas diffusion electrode of the present invention, a gas diffusion electrode that can suppress water flooding while ensuring sufficient drainage of the microporous layer surface without impairing gas diffusion and conductivity can be obtained. Detailed Implementation

[0027] The preferred embodiments of the gas diffusion electrode of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be implemented in various ways according to the purpose and use.

[0028] The gas diffusion electrode of the present invention (hereinafter sometimes referred to as the gas diffusion electrode of the present invention) is a gas diffusion electrode having a "microporous layer containing carbonaceous particles and a fluorinated hydrophobic resin" on at least one side of a conductive porous substrate (e.g., at least one end face of the two end faces in the thickness direction of the conductive porous substrate). In the gas diffusion electrode of the present invention, the surface F / C of the microporous layer on the side that is not in contact with the conductive porous substrate is 0.35 or more and 0.60 or less. This surface F / C is the ratio of fluorine to carbon, measured by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) at an accelerating voltage of 2.0 kV and a field of view of 1000x on the surface of the microporous layer. The surface of the microporous layer is, for example, the end face of the two end faces in the thickness direction of the microporous layer that is not in contact with the conductive porous substrate.

[0029] As the conductive porous substrate used in the gas diffusion electrode of the present invention (hereinafter sometimes referred to as the conductive porous substrate of the present invention), it is preferable to use porous substrates containing carbon fibers, such as carbon fiber fabric, carbon fiber paper, carbon fiber nonwoven fabric, carbon felt, carbon paper, carbon cloth, etc., as well as porous metal substrates such as foamed sintered metal, metal mesh, expanded metal, etc. Among them, porous substrates containing carbon fibers are preferred because of their excellent corrosion resistance. In particular, due to their excellent properties of absorbing dimensional changes in the thickness direction of the electrolyte membrane, i.e., "elasticity", it is more preferable to use a substrate containing resin carbides, i.e., carbon paper, which is obtained by bonding carbon fiber paper with resin carbides.

[0030] Furthermore, as the conductive porous substrate used in the gas diffusion electrode of the present invention, a conductive porous substrate that has undergone hydrophobic treatment is preferably used. As the method of hydrophobic treatment, a method of applying a hydrophobic resin is preferred. Examples of hydrophobic resins that can be applied to the conductive porous substrate of the present invention include fluorinated hydrophobic resins such as PTFE (polytetrafluoroethylene) (e.g., "Teflon" (registered trademark)), FEP (tetrafluoroethylene / hexafluoropropylene copolymer), PFA (perfluoroalkoxy fluorinated resin), ETFE (ethylene / tetrafluoroethylene copolymer), PVDF (polyvinylidene fluoride), and PVF (polyvinylidene fluoride). Among these, PTFE or FEP, which exhibit strong hydrophobicity, are preferred.

[0031] There is no particular limitation on the amount of hydrophobic resin imparted through hydrophobic treatment. When the total mass of the hydrophobically treated conductive porous substrate is set at 100% by mass, a content of approximately 0.1% to 20% by mass of hydrophobic resin in the conductive porous substrate is appropriate. If the content of hydrophobic resin (the ratio of the mass of hydrophobic resin to the total mass of the conductive porous substrate) is less than 0.1% by mass, the hydrophobicity may not be fully realized. If the content of hydrophobic resin exceeds 20% by mass, it may sometimes clog the pores that serve as gas diffusion or drainage paths, or cause an increase in resistance.

[0032] As a method for hydrophobic treatment of conductive porous substrates, in addition to the commonly known method of impregnating the conductive porous substrate in a dispersion containing a hydrophobic resin, methods such as die coating or spraying can also be used to coat the conductive porous substrate with a hydrophobic resin. Alternatively, dry processes such as sputtering of fluororesins can also be used. Furthermore, after the above-mentioned hydrophobic treatment, a drying process and then a sintering process can be performed as needed.

[0033] As described above, the gas diffusion electrode of the present invention is configured to have a microporous layer on at least one side of a conductive porous substrate. In the present invention, a microporous layer is a layer with pores, such as a layer containing carbonaceous particles such as carbon black, carbon nanotubes, carbon nanofibers, chopped carbon fibers, graphene, or graphite. The microporous layer (hereinafter sometimes referred to as the microporous layer of the present invention) may also contain other conductive materials as needed.

[0034] Carbon black is preferred as the carbonaceous particles contained in the microporous layer of the present invention due to its low cost and stable product quality. Examples of carbon black include furnace black, acetylene black, Ketjen black, channel black, and lampblack. Among these carbon blacks, acetylene black is preferred from the viewpoint of having fewer impurities and minimizing the reduction of catalyst activity. Furthermore, ash content can be used as a benchmark for the impurity content in carbon black. When the total mass of carbon black is set as 100% by mass, carbon black with an ash content of 0.1% by mass or less is preferred. Moreover, the lower the ash content in the carbon black, the more preferred it is; carbon black with an ash content of 0% by mass, i.e., carbon black without ash, is particularly preferred.

[0035] Furthermore, the microporous layer of the present invention requires good drainage. Therefore, in addition to containing carbonaceous particles, the microporous layer of the present invention also contains a fluorinated hydrophobic resin. Here, a fluorinated hydrophobic resin refers to a hydrophobic resin containing fluorine atoms in its molecule. Examples of fluorinated hydrophobic resins include PTFE, FEP, PFA, ETFE, PVDF, and PVF. Among these, PTFE or FEP is preferred from the viewpoint of particularly high hydrophobicity.

[0036] The mass of the fluorinated hydrophobic resin contained in the microporous layer of the present invention is preferably 20% by mass or more, more preferably 25% by mass or more, when the total mass of the microporous layer is set to 100% by mass. When the mass of the fluorinated hydrophobic resin contained in the microporous layer of the present invention is less than 20% by mass, the hydrophobicity may not be fully utilized, leading to water flooding. Furthermore, the mass of the fluorinated hydrophobic resin contained in the microporous layer of the present invention is preferably 45% by mass or less, more preferably 40% by mass or less, when the total mass of the microporous layer is set to 100% by mass. When the mass of the fluorinated hydrophobic resin contained in the microporous layer of the present invention is greater than 45% by mass, the conductivity of the microporous layer may sometimes decrease.

[0037] The mass of the fluorinated hydrophobic resin contained in the microporous layer of the present invention can be derived, for example, by the method shown below. First, the surface of the microporous layer of the gas diffusion electrode is scraped with a scraper or the like, and the resulting microporous layer powder is sintered at 500°C for about 2 hours using an electric furnace or similar device. This decomposes and removes the fluorinated hydrophobic resin from the microporous layer powder. The mass of the target fluorinated hydrophobic resin can be calculated by dividing the difference in mass of the microporous layer powder before and after heating by the mass of the microporous layer powder before heating.

[0038] The microporous layer of the present invention is preferably formed by coating a conductive porous substrate with a coating liquid for forming a microporous layer, followed by drying and sintering. The coating liquid for forming a microporous layer referred to herein is a liquid in which carbonaceous particles, fluorinated hydrophobic resins, etc., which should be contained in the microporous layer are dispersed in a dispersion medium.

[0039] In the drying of the coating liquid for forming a microporous layer, in order to maintain the smoothness of the microporous layer surface while promoting the migration of the fluorohydrophobic resin within the coating liquid and simultaneously evaporating the dispersion medium, drying is preferably carried out at a temperature of 100°C or higher and 200°C or lower. When the drying temperature is below 100°C, the evaporation of the dispersion medium is insufficient, and migration may not be promoted. When the drying temperature exceeds 200°C, the smoothness of the microporous layer surface may be lost due to rapid evaporation of the dispersion medium. A lower limit for this drying temperature is more preferably 120°C or higher. An upper limit for this drying temperature is more preferably 180°C or lower.

[0040] Furthermore, in the sintering of the coating liquid for forming the microporous layer, in order to melt the fluorinated hydrophobic resin on the surface of the microporous layer, sintering is preferably carried out at a temperature of 325°C or higher, and more preferably at a temperature of 350°C or higher. When the sintering temperature is lower than 325°C, the melting of the fluorinated hydrophobic resin becomes insufficient, which may sometimes lead to reduced drainage and water flooding.

[0041] The coating liquid for forming a microporous layer preferably contains, in addition to the aforementioned carbonaceous particles and fluorinated hydrophobic resin, a dispersion medium and a dispersant for promoting the dispersion of the carbonaceous particles. Regarding the amount of this dispersant, it is preferable that the mass ratio of the dispersant to the mass of the carbonaceous particles contained in the coating liquid for forming a microporous layer is 0.1 or more. If the mass ratio of the dispersant is less than 0.1, the dispersion of the carbonaceous particles may sometimes fail. Furthermore, without impairing the dispersion of the carbonaceous particles, other substances such as thickeners and defoamers may be added to the coating liquid for forming a microporous layer as needed.

[0042] Water is preferred as the dispersion medium. Other dispersion media may include water-soluble organic solvents such as alcohols. One or more of these dispersion media may be used.

[0043] Examples of nonionic surfactants that can be used as dispersants include polyoxyethylene alkyl ethers, polyoxyethylene alkenyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, polyoxyethylene phenyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene polystyrene phenyl ethers, polyoxyethylene naphthyl ethers, polyoxyethylene alkylamines, polyoxyethylene alkylamides, polyoxyethylene polyoxypropylene glycol, polyoxyethylene fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, and polyoxyethylene glycerol ethers. One or more of these can be used as dispersants. From the viewpoint of good dispersibility of carbonaceous particles, polyoxyethylene alkyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, polyoxyethylene alkylphenyl ethers, and polyoxyethylene polystyrene phenyl ethers are preferred.

[0044] As the aforementioned thickener, water-soluble polymers such as methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, polyacrylic acid, polylactic acid, guar gum, xanthan gum, and starch can be used. Furthermore, as the aforementioned defoamer, polysiloxanes and phosphate esters can be used.

[0045] As a method for coating a microporous layer on a conductive porous substrate of the present invention, it is preferable to use a coating method such as screen printing, rotary screen printing, spraying, intaglio printing, gravure printing, die coating machine printing, bar coating, blade coating, knife coating, etc.

[0046] The thickness of the conductive porous substrate of the present invention is preferably 120 μm or more and 200 μm or less. When the thickness of the conductive porous substrate of the present invention is preferably 120 μm or more, more preferably 130 μm or more, the in-plane gas diffusion is easily improved, and the mechanical strength of the gas diffusion electrode can be improved. In addition, when the thickness of the conductive porous substrate of the present invention is preferably 200 μm or less, more preferably 160 μm or less, the conductive path is easily connected, and the conductivity can be effectively improved. The thickness of the conductive porous substrate of the present invention can be measured by a digital micrometer.

[0047] Furthermore, the thickness of the microporous layer of the present invention is preferably 10 μm or more and 120 μm or less. When the thickness of the microporous layer of the present invention is preferably 120 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less, the gas diffusion electrode itself exhibits excellent gas or water diffusivity (permeability or drainage), effectively reducing resistance. Additionally, the thickness of the microporous layer of the present invention is preferably 10 μm or more, more preferably 20 μm or more, thereby covering the roughness of the conductive porous substrate. The thickness of the microporous layer of the present invention can be calculated by measuring the thickness of the gas diffusion layer and the thickness of the conductive porous substrate using a digital micrometer, and then subtracting the thickness of the conductive porous substrate from the obtained thickness of the gas diffusion layer.

[0048] The unit area weight (mass per unit area) of the microporous layer of the present invention is preferably 10 g / m². 2 Above and 30g / m 2 Within the following range, the unit area weight of the microporous layer of the present invention is 10 g / m². 2 When the above conditions are met, the surface of the conductive porous substrate can be reliably covered, promoting the reverse diffusion of generated water, thus improving power generation performance. The unit area weight of the microporous layer of the present invention is more preferably 14 g / m².2 The above is further preferred to be 16g / m 2 That's all. Additionally, if the unit area weight of the microporous layer of the present invention is 30 g / m²... 2 This process suppresses clogging of recesses and pores, further improving drainage. The more preferably, the weight per unit area of ​​the microporous layer of the present invention is 26 g / m². 2 The following is a further preferred value: 24 g / m 2 The following is a further explanation. Additionally, the weight per unit area of ​​the gas diffusion electrode of the present invention, to which the microporous layer is formed, is preferably 30 g / m². 2 Above and 90g / m 2 Within the following range.

[0049] The density of the conductive porous substrate of the present invention is preferably 0.15 g / cm³. 3 Above and 0.50 g / cm 3 Within the following range. The density of the conductive porous substrate of the present invention is made to be 0.15 g / cm³. 3 The above methods can significantly improve the strength of the conductive porous substrate and effectively enhance its durability. This is achieved by setting the density of the conductive porous substrate of the present invention to 0.50 g / cm³. 3 The following measures can prevent a decrease in drainage and gas diffusion.

[0050] The surface layer F / C of the gas diffusion electrode of the present invention on the side that is not in contact with the conductive porous substrate is 0.35 or more and 0.60 or less. The surface layer F / C is the ratio of fluorine to carbon, which is measured by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) at an accelerating voltage of 2.0 kV and a field of view of 1000x.

[0051] Here, the method for determining the surface F / C ratio, namely SEM-EDX, in this invention is described in more detail. In SEM-EDX, the surface that is not in contact with the conductive porous substrate, one side of the microporous layer coated with platinum at a thickness of 1.0 nm, is first observed using a scanning electron microscope (SEM) at 1000x magnification. The observed surface is then irradiated with an electron beam at an accelerating voltage of 2.0 kV using energy-dispersive X-ray diffraction (EDX), and the characteristic X-rays reflected from the observed surface are detected. Based on the detected characteristic X-rays, the fluorine and carbon content in the observed surface is determined, and the fluorine / carbon content ratio is calculated based on the measured values, thereby obtaining the surface F / C ratio. At this point, since the detection depth is several hundred nm to several μm, the surface F / C ratio measured by SEM-EDX quantifies the content of fluorine and carbon elements in the surface layer of the microporous layer, within a distance of several hundred nm to several μm from the side of the surface that is not in contact with the conductive porous substrate. This is an indicator of the degree of migration of the fluorinated hydrophobic resin. The migration of the fluorinated hydrophobic resin refers to the phenomenon where, after the microporous layer forming coating solution is applied to the conductive porous substrate, as the dispersion medium in the coating solution dries, the fluorinated hydrophobic resin moves towards the side of the microporous layer that is not in contact with the conductive porous substrate.

[0052] The surface F / C ratio can also be controlled by adjusting the mass of the fluoropolymer hydrophobic resin in the microporous layer. However, when the mass of the fluoropolymer hydrophobic resin is high, the conductivity of the microporous layer may decrease. Therefore, as a method to control the surface F / C ratio, it is preferable to control the migration of the fluoropolymer hydrophobic resin by adjusting the drying conditions and the viscosity of the coating solution for forming the microporous layer. As a method to control the migration of the fluoropolymer hydrophobic resin, it is preferable to control the migration of the fluoropolymer hydrophobic resin by controlling the drying conditions such as drying temperature and drying time. In addition, it is also preferable to control the migration by adjusting the viscosity of the mixed solution containing carbonaceous particles and components other than the fluoropolymer hydrophobic resin in the coating solution for forming the microporous layer, thereby changing the resistance to the movement of the fluoropolymer hydrophobic resin. Furthermore, it is more preferable to use a combination of these two methods to control the migration of the fluoropolymer hydrophobic resin.

[0053] If the surface layer F / C is 0.35 or higher, preferably 0.40 or higher, then a large amount of fluorinated hydrophobic resin exists in the surface layer of the microporous layer, which can effectively improve drainage. If the surface layer F / C is 0.60 or lower, preferably 0.55 or lower, then the conductivity of the microporous layer can be sufficiently maintained.

[0054] In the gas diffusion electrode of the present invention, the F / C ratio of the outermost 10 nm layer on the surface of the microporous layer that is not in contact with the conductive porous substrate is preferably 0.62 or higher and 0.80 or lower. This F / C ratio of the outermost 10 nm layer is determined by X-ray photoelectron spectroscopy (ESCA) on the surface of the microporous layer when the excitation X-rays are monochromatic AlKα. 1,2 The ratio of fluorine to carbon was determined under conditions of X-ray (1486.6 eV), X-ray beam diameter of 200 μm, and photoelectron detection angle of 45°.

[0055] Here, the method for determining the F / C of the outermost 10 nm layer in this invention, namely X-ray photoelectron spectroscopy (ESCA), will be described in more detail.

[0056] In ESCA, the surface of the microporous layer that is not in contact with the conductive porous substrate is first examined using Quantera SXM with monochromatic Al Kα X-rays. 1,2 X-rays were applied under conditions of 1486.6 eV, an X-ray beam diameter of 200 μm, and a photoelectron detection angle of 45°. The photoelectrons emitted from the surface were detected using an analyzer. The detection data were smoothed using a 9-point smoothing method, and the data was processed with the C1s main peak (CHx, CC, C=C) corrected for the horizontal axis at 284.6 eV. The F / C ratio of the outermost 10 nm layer was calculated by dividing the resulting fluorine percentage (%) by the carbon percentage (%). The detection depth of ESCA can be controlled by the photoelectron detection angle. Using the above conditions, the content of fluorine and carbon elements up to a depth of 10 nm on the side of the microporous layer that is not in contact with the conductive porous substrate can be quantified. The F / C ratio of the outermost 10 nm layer obtained by the above determination can be used as an indicator of the fluorine content in the outermost 10 nm layer itself, but it can also be used as an indicator of the increased surface area due to the melting of the fluorinated hydrophobic resin at high temperatures. That is, even when the microporous layer contains the same amount of fluorinated hydrophobic resin, if the F / C of the outermost 10 nm layer is large, the surface of the microporous layer that is not in contact with the conductive porous substrate will also exhibit high hydrophobicity.

[0057] The F / C ratio of the outermost 10 nm layer can also be improved by adjusting the mass of the fluoropolymer hydrophobic resin in the microporous layer. However, if only the mass of the fluoropolymer hydrophobic resin is high, the conductivity of the microporous layer may sometimes decrease. Therefore, similar to the method described above for adjusting the surface F / C, it is preferable to adjust the F / C ratio of the outermost 10 nm layer by controlling the migration of the fluoropolymer hydrophobic resin. Furthermore, it is even more preferable to increase the surface area of ​​the fluoropolymer hydrophobic resin within the outermost 10 nm range by subjecting the fluoropolymer hydrophobic resin that has migrated to the surface to sufficient heat to melt it. This is because it further improves the F / C ratio of the outermost 10 nm layer.

[0058] The F / C ratio of the outermost 10 nm layer is preferably 0.62 or higher, more preferably 0.66 or higher. When the F / C ratio of the outermost 10 nm layer is lower than 0.62, the amount of fluoropolymer hydrophobic resin on the outermost surface of the microporous layer decreases, which may sometimes result in insufficient drainage. The F / C ratio of the outermost 10 nm layer is preferably 0.80 or lower, more preferably 0.76 or lower. When the F / C ratio of the outermost 10 nm layer is greater than 0.80, the fluoropolymer hydrophobic resin on the outermost surface of the microporous layer may hinder conductive pathways, which may sometimes result in reduced conductivity.

[0059] Furthermore, in the gas diffusion electrode of the present invention, the O / C ratio of the outermost 10 nm of the surface of the microporous layer that is not in contact with the conductive porous substrate is preferably 0.01 or less. This O / C ratio of the outermost 10 nm is determined by X-ray photoelectron spectroscopy (ESCA) on the surface of the microporous layer when the excitation X-rays are monochromatic AlKα. 1,2 The oxygen-to-carbon ratio was determined under conditions of X-ray beam diameter of 200 μm and photoelectron detection angle of 45°, using 1486.6 eV. The O / C ratio of the outermost 10 nm layer can be calculated by obtaining the percentage of fluorine and oxygen under the same conditions as those used to determine the F / C ratio of the outermost 10 nm layer. An O / C ratio greater than 0.01 in the outermost 10 nm layer indicates the presence of dispersants, thickeners, and defoamers from the coating solution used to form the microporous layer on the surface, which may sometimes reduce water permeability. The O / C ratio of the outermost 10 nm layer can be reduced by decreasing the content of dispersants, thickeners, and defoamers in the coating solution used to form the microporous layer, or by increasing the sintering time and temperature to promote their decomposition.

[0060] The gas diffusion electrode of the present invention preferably has a resistance in the normal direction of 5.5 mΩ·cm when compressed under a pressure of 2.4 MPa. 2 Below. When the resistance is greater than 5.5 mΩ·cm 2When a gas diffusion electrode is used as a component of a fuel cell, conductivity is impeded, which can sometimes reduce initial power generation performance.

[0061] In this invention, the contact angle between the surface of the microporous layer that is not in contact with the conductive porous substrate and the mixture of isopropanol and water at a mass ratio of 1:2 is preferably 35° or more and 80° or less. When the contact angle is less than 35°, the drainage performance of the gas diffusion electrode is poor, and water flooding may sometimes occur. When the contact angle is greater than 80°, the drainage performance is too high, resulting in a dry environment for the gas electrode substrate, which may sometimes reduce the power generation performance. This contact angle can be controlled by adjusting the F / C ratio of the surface layer and the F / C ratio of the outermost 10 nm layer.

[0062] Example

[0063] The present invention is illustrated below using examples and comparative examples, but the present invention is not limited to the following examples.

[0064] [Determination Method]

[0065] (1) Surface F / C

[0066] In the determination of the surface fluorine (F / C) ratio, a platinum coating with a thickness of 1.0 nm was first formed on the side of the microporous layer that is not in contact with the conductive porous substrate. This surface was then observed using a SEM (Hitachi High Technology Co., Ltd. cold cathode field emission scanning electron microscope S-4800) at 1000x magnification for elemental distribution analysis. In the elemental distribution analysis, EDX (Bruker AXS QUANTAX Flat QUAD system Wflash 5060FQ) was used to detect and quantify the characteristic X-rays reflected from an electron beam irradiated at an accelerating voltage of 2.0 kV, thereby calculating the fluorine and carbon content of the surface. The surface F / C ratio of the target was calculated by dividing the calculated fluorine content by the carbon content.

[0067] (2) The F / C ratio of the outermost 10nm layer

[0068] In the determination of the F / C ratio of the outermost 10 nm layer, the surface of the microporous layer not in contact with the conductive porous substrate was first measured using X-ray photoelectron spectroscopy (ESCA) with a Quantera SXM (manufactured by PKI). As the measurement conditions at this stage, the excitation X-rays were monochromatic Al Kα. 1,2X-ray beam diameter was 200 μm, and photoelectron detection angle was 45° (1486.6 eV). Data processing employed 9-point smoothing, with the C1s main peak (CHx, CC, C=C) corrected at 284.6 eV for the horizontal axis. The F / C ratio of the outermost 10 nm of the target was calculated by dividing the fluorine percentage (%) determined by ESCA by the carbon percentage (%).

[0069] (3) The outermost 10nm O / C

[0070] The O / C ratio of the outermost 10 nm layer was determined by X-ray photoelectron spectroscopy (ESCA) in the same manner as the F / C ratio of the outermost 10 nm layer mentioned above (2). The O / C ratio of the outermost 10 nm layer, which was the target, was calculated by dividing the oxygen ratio (%) obtained by ESCA by the carbon ratio (%).

[0071] (4) Resistance in the normal direction of the gas diffusion electrode

[0072] In this measurement, a gas diffusion electrode was cut to a size of 20 mm × 20 mm, and the cut gas diffusion electrode was clamped from top to bottom by smooth, gold-plated metal rigid electrodes. Then, an average pressure of 2.4 MPa was applied to the gas diffusion electrode via these upper and lower rigid electrodes. Under this condition, the voltage between the upper and lower rigid electrodes was measured when a current of 1 A flowed through them, thereby calculating the resistance per unit area in the normal direction of the target gas diffusion electrode.

[0073] (5) Contact angle of gas diffusion electrode

[0074] In this measurement, firstly, under an environment of 20°C and 60% humidity, 5 μL droplets of a mixture of isopropanol and water at a mass ratio of 1:2 were dropped onto 10 randomly selected locations on the surface of the microporous layer that were not in contact with the conductive porous substrate. Then, for each droplet at each point on the surface, the contact angle between the surface and the water droplet was measured using an automatic contact angle meter DM-501 (manufactured by Kyowa Interface Science Co., Ltd.). The average value of the obtained contact angles was taken as the contact angle of the gas diffusion electrode.

[0075] [Example 1]

[0076] (Conductive porous substrate)

[0077] In Example 1, polyacrylonitrile carbon fibers (Toray Corporation's "Torayca (registered trademark)" T300) with an average diameter of 7 μm were first cut into average lengths of 12 mm. The cut carbon fibers were dispersed in water and papermaking was carried out continuously using a wet papermaking method.

[0078] On the papermaking body obtained as described above, a 10% by mass aqueous solution of polyvinyl alcohol as a binder is coated and dried to produce carbon fiber with a unit area weight of 15 g / m². 2 The carbon fiber sheet. At this point, the amount of polyvinyl alcohol attached is 20 parts by mass relative to 100 parts by mass of the carbon fiber.

[0079] Next, "phenolic resin prepared by mixing methyl phenolic resin and linear phenolic resin in a mass ratio of 1:1 for non-volatile components", flake graphite powder (average particle size 5 μm) and methanol are mixed in a mass ratio of 10 / 5 / 85 to uniformly disperse them, thereby obtaining a resin composition.

[0080] Next, the carbon fiber sheet is continuously impregnated in the resin composition. This impregnation process involves clamping and pressing the impregnated carbon fiber sheet with rollers, followed by winding into a roll to obtain a carbon fiber sheet with a precursor. At this point, two smooth metal rollers with a structure capable of removing excess resin composition with a scraper are arranged horizontally with a certain gap between them. The carbon fiber sheet with the precursor is passed horizontally between these two rollers and then lifted vertically upwards, thereby adjusting the overall amount of resin composition adhered to the carbon fiber sheet with the precursor. The amount of phenolic resin adhered to the carbon fiber sheet with the precursor is 130 parts by weight relative to 100 parts by weight of carbon fiber sheet.

[0081] On a flatbed press, hot plates are arranged parallel to each other, with spacers placed on the lower hot plate to maintain a constant spacing between them. The aforementioned carbon fiber sheet with the precursor is then clamped between release paper, and the clamped carbon fiber sheet with the precursor is heated and pressurized. Afterwards, the carbon fiber sheet with the precursor is introduced into a furnace under a nitrogen atmosphere for sintering and carbonization, thereby obtaining the conductive porous substrate of Example 1. The resulting conductive porous substrate has a thickness of 140 μm and a density of 0.30 g / cm³ under a pressure of 0.15 MPa. 3 .

[0082] (Hydrophobic finish)

[0083] In Example 1, a diluted aqueous solution of PTFE dispersion (“Polyflon (registered trademark)” D-210C; manufactured by Daikin Industries, Ltd.; the dispersion medium (water) contains 60% by mass of PTFE) was applied to the aforementioned conductive porous substrate using a slot die coater, such that PTFE was applied in an amount of 5.0 parts by mass relative to 100.0 parts by mass of the conductive porous substrate. Subsequently, the conductive porous substrate was subjected to a hydrophobic treatment by drying the coating solution on the conductive porous substrate at 120°C.

[0084] (Coating solution for forming microporous layers)

[0085] Next, a coating solution for forming a microporous layer was prepared using acetylene black (“Denka Black”; manufactured by Denka Corporation) as carbon black, a PTFE dispersion (“Polyflon” D-210C, a registered trademark) as a hydrophobic agent, Triton X-100 (manufactured by NacalaiTesque) as a dispersant, and purified water. At this time, the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was adjusted to 8.0 parts by mass / 7.0 parts by mass / 7.0 parts by mass / 78.0 parts by mass to prepare the coating solution for forming a microporous layer. The mass ratio of PTFE to the solid components (acetylene black and PTFE) in the resulting coating solution for forming a microporous layer was 0.34.

[0086] (Coating and drying)

[0087] The resulting microporous layer forming coating solution was applied to the hydrophobically treated conductive porous substrate using a slit-die coating machine. At this point, the solid content of the microporous layer forming coating solution was 14 g / m². 2 The coating liquid for forming a microporous layer is applied in a specific manner. Then, the coating liquid for forming a microporous layer on the conductive porous substrate is dried at 140°C.

[0088] (sintering)

[0089] Next, the dried components of the conductive porous substrate and the coating liquid for forming the microporous layer were sintered at a temperature of 365°C to obtain the gas diffusion electrode of Example 1.

[0090] For the gas diffusion electrode of Example 1 obtained in this way, the above-mentioned (1) surface F / C, (2) F / C of the outermost 10 nm, (3) O / C of the outermost 10 nm, (4) resistance in the normal direction of the gas diffusion electrode, and (5) contact angle of the gas diffusion electrode were measured according to their respective measurement methods. The evaluation results of Example 1 are shown in Table 1 described below.

[0091] [Example 2]

[0092] In Example 2, the gas diffusion electrode was obtained in the same manner as in Example 1, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 7.0 parts by mass / 9.0 parts by mass / 76.0 parts by mass. The evaluation results of Example 2 are shown in Table 1.

[0093] [Example 3]

[0094] In Example 3, the gas diffusion electrode was obtained in the same manner as in Example 1, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 7.0 parts by mass / 11.0 parts by mass / 74.0 parts by mass. The evaluation results of Example 3 are shown in Table 1.

[0095] [Example 4]

[0096] In Example 4, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 7.0 parts by mass / 13.0 parts by mass / 72.0 parts by mass, the gas diffusion electrode was obtained in the same manner as in Example 1. The evaluation results of Example 4 are shown in Table 1.

[0097] [Example 5]

[0098] In Example 5, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 11.0 parts by mass / 7.0 parts by mass / 74.0 parts by mass, a gas diffusion electrode was obtained in the same manner as in Example 1. The evaluation results of Example 5 are shown in Table 1.

[0099] [Example 6]

[0100] In Example 6, the gas diffusion electrode was obtained in the same manner as in Example 1, except that the sintering temperature was set to 320°C, and various measurements were performed. The evaluation results of Example 6 are shown in Table 1.

[0101] [Example 7]

[0102] In Example 7, except that the composition of the coating solution for forming the microporous layer was adjusted to a mass ratio of acetylene black / hydrophobic agent / dispersant / purified water of 8.0 parts by mass / 7.0 parts by mass / 15.0 parts by mass / 70.0 parts by mass, and the drying temperature after coating the microporous layer was set to 180°C, a gas diffusion electrode was obtained in the same manner as in Example 1. The evaluation results of Example 7 are shown in Table 1.

[0103] [Example 8]

[0104] In Example 8, the gas diffusion electrode was obtained in the same manner as in Example 1, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 9.0 parts by mass / 15.0 parts by mass / 68.0 parts by mass. The evaluation results of Example 8 are shown in Table 1.

[0105] [Example 9]

[0106] In Example 9, except that the drying temperature after coating with the microporous layer-forming solution was set to 180°C, a gas diffusion electrode was obtained in the same manner as in Example 1, and various measurements were performed. The evaluation results of Example 9 are shown in Table 2 below.

[0107] [Example 10]

[0108] In Example 10, a gas diffusion electrode was obtained in the same manner as in Example 1, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 11.0 parts by mass / 15.0 parts by mass / 66.0 parts by mass. The evaluation results of Example 10 are shown in Table 2.

[0109] [Comparative Example 1]

[0110] In Comparative Example 1, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 7.0 parts by mass / 15.0 parts by mass / 70.0 parts by mass, a gas diffusion electrode was obtained in the same manner as in Example 1. The evaluation results of Comparative Example 1 are shown in Table 2.

[0111] [Comparative Example 2]

[0112] In Comparative Example 2, except that the composition of the coating solution for forming the microporous layer was adjusted to a mass ratio of acetylene black / hydrophobic agent / dispersant / purified water of 8.0 parts by mass / 7.0 parts by mass / 15.0 parts by mass / 70.0 parts by mass, and the drying temperature after coating the microporous layer was set to 100°C, a gas diffusion electrode was obtained in the same manner as in Example 1, and various measurements were performed. The evaluation results of Comparative Example 2 are shown in Table 2.

[0113] [Comparative Example 3]

[0114] In Comparative Example 3, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 2.0 parts by mass / 7.0 parts by mass / 83.0 parts by mass, a gas diffusion electrode was obtained in the same manner as in Example 1. The evaluation results of Comparative Example 3 are shown in Table 2.

[0115] [Comparative Example 4]

[0116] In Comparative Example 4, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 25.0 parts by mass / 7.0 parts by mass / 60.0 parts by mass, a gas diffusion electrode was obtained in the same manner as in Example 1. The evaluation results of Comparative Example 4 are shown in Table 2.

[0117] [Comparative Example 5]

[0118] In Comparative Example 5, except that the composition of the coating solution for forming the microporous layer was adjusted so that the mass ratio of acetylene black / hydrophobic agent / dispersant / purified water was 8.0 parts by mass / 7.0 parts by mass / 20.0 parts by mass / 65.0 parts by mass, a gas diffusion electrode was obtained in the same manner as in Example 1. The evaluation results of Comparative Example 5 are shown in Table 2.

[0119]

[0120]

[0121] Industry availability

[0122] As described above, the gas diffusion electrode of the present invention is suitable for use as an electrode in fuel cells. In fuel cells, the gas diffusion electrode of the present invention is particularly well suited for use as an electrode in polymer electrolyte fuel cells used as power sources for transportation equipment such as fuel cell vehicles and fuel cell aircraft.

Claims

1. A gas diffusion electrode, characterized in that, The conductive porous substrate has a microporous layer containing carbonaceous particles and a fluorinated hydrophobic resin on at least one side. The surface F / C ratio of the microporous layer on the side that is not in contact with the conductive porous substrate is greater than 0.35 and less than 0.

60. The surface F / C is the ratio of fluorine to carbon, which is determined by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) at an accelerating voltage of 2.0 kV and a field of view of 1000x.

2. The gas diffusion electrode as described in claim 1, characterized in that, The outermost 10 nm of the surface of the microporous layer, on the side not in contact with the conductive porous substrate, has an F / C ratio of 0.62 or higher and 0.80 or lower. The F / C of the outermost 10 nm is determined by X-ray photoelectron spectroscopy (ESCA) under monochromatic AlKα excitation at 1486.6 eV. 1,2 The ratio of fluorine to carbon was determined under conditions of 200 μm X-ray beam diameter and 45° photoelectron detection angle.

3. The gas diffusion electrode as described in claim 1, characterized in that, The outermost 10 nm of the surface of the microporous layer, on the side not in contact with the conductive porous substrate, has an O / C ratio of less than 0.

01. This O / C ratio is determined by X-ray photoelectron spectroscopy (ESCA) using monochromatic AlKα excitation at 1486.6 eV. 1,2 The ratio of oxygen to carbon was determined under conditions of 200 μm X-ray beam diameter and 45° photoelectron detection angle.

4. The gas diffusion electrode as described in claim 1, characterized in that, The resistivity in the normal direction during compression at a pressure of 2.4 MPa is 5.5 mΩ·cm. 2 the following.

5. The gas diffusion electrode as described in claim 1, characterized in that, The contact angle between the surface of the microporous layer that is not in contact with the conductive porous substrate and the mixture of isopropanol and water in a mass ratio of 1:2 is greater than 35° and less than 80°.

Citation Information

Patent Citations

  • Gas diffusion electrode, fuel cell, and transportation device

    WO2023190153A1